The Effect Of Shopping Emotion And Perceived Risk On Purchasing Decisions Through Impulsive Buying As An Intervening Variable In Shopee E-Commerce Consumers - Marhadi Marhadi; Gustina Adinda Putri; Aida Nursanti; Cifebrima Suyastri (Enrichment : Journal of Management, 2022)
The research was conducted with the aim of knowing the effect of shopping emotion and perceived risk on purchasing decisions through impulsive buying on E-Commerce Shopee consumers in Pekanbaru City. Questionnaires were distributed to 126 respondents using the Purposive Sampling technique and processed using the Structural Equation Modeling – Partial Least Square analysis method with SmartPLS software version 3.2.9.The results showed that there was a positive and significant influence between shopping emotion on purchasing decisions. There is a positive and significant effect between shopping emotion on impulsive buying. There is a positive and significant influence between perceived risk on purchasing decisions. There is a positive and significant effect between perceived risk on impulsive buying. There is a positive and significant influence between impulsive buying on purchasing decisions.